TEACHING VOCABULARY THROUGH MEDIA “CRAZY FACE” AT ELEMENTARY SCHOOL STUDENTS - Diana Mustika Wati; An Fauzia Rozani Sy. (Universitas Negeri Padang, 2013)
ABSTRAK This article discussed about the learning media which is unique and little bit crazy. Through this crazy face media, students will be directed to write the vocabulary in English. In the beginning of learning process, teacher will show the media (picture) to the students. Furthermore, the teacher will show how to pronounce and write the word on the picture. Crazy face media is intended to help the teacher for teaching english to young learner. Besides that the students are hoped to be motivated in learning english and they will change their opinion about the difficulties of learning vocabularies. Key words: Vocabulary, Media crazy face